Mesenchymal stem cells in non-small cell lung cancer - different from others?: Insights from comparative molecular and functional analyses - Gottschling, Sandra; Granzow, Martin; Kuner, Ruprecht; Jauch, Anna; Herpel, Esther; Chang Xu, Elizabeth; Muley, Thomas; Schnabel, Philipp Albert; Herth, Felix; Meister, Michael (Lung cancer, 2013)
Background - Cancer-associated fibroblasts (CAF) play a vital role in lung cancer initiation and progression. Although mesenchymal stem cells (MSC) are considered progenitor cells of fibroblasts and show cancer modulating abilities themselves, analyses on their presence and properties in lung cancer are lacking so far. - Methods - We performed a comparative molecular and functional analysis of MSC derived from non-small cell lung cancer (NSCLC) and corresponding normal lung tissue (NLT) of a total of 15 patients. MSC were identified and selected according to their mesenchymal multilineage differentiation capability and surface marker profile. - Results - Compared to NLT-MSC, NSCLC-MSC showed accelerated growth kinetics and reduced sensitivity to cisplatin. Karyotyping, comparative genomic hybridization and multiplex fluorescence in situ hybridization revealed no chromosomal aberrations. However, gene expression profiling of NSCLC- and NLT-MSC indicated variable expression of 62 genes involved in proliferation, DNA repair, apoptosis, extracellular matrix synthesis, tissue remodeling and angiogenesis. Differential expression of the selected candidate genes butyrylcholinesterase, clusterin and quiescin Q6 sulfhydryl oxidase 1 was validated by quantitative real-time PCR and, on protein level, by immunohistochemical analyses of original tumor tissue. Upon exposure to tumor cell-conditioned medium or transforming growth factor-β, both, NSCLC-MSC and NLT-MSC acquired expression of α-smooth muscle actin (α-SMA), a major characteristics of CAF. - Conclusions - This study indicates that NSCLC tissue contains MSC with specific molecular and functional properties. These cells might represent a progenitor reservoir for CAF and thus crucially contribute to lung cancer progression.
Gesehen am 24.02.2020